Intellectual Capital and Corporate Performance of Technology-Intensive Companies: Malaysia Evidence - Kin, G.; Saleh, Z. (Faculty of Business and Accountancy, University of Malaya, 2008)
This paper examines the association between Intellectual Capital (IC) and corporate performance of technology-intensive companies (MESDAQ) listed on Bursa Malaysia by investigating whether value creation efficiency, as measured by Value Added Intellectual Capital (VAICTM), can be explained by market valuation, profitability, and productivity. Correlation and regression models were used to examine the relationship between corporate value creation efficiency and firms? market valuation, profitability and productivity. The findings from this study show that technology-intensive companies still depend very much on physical capital efficiency. The study also suggests that individually, each component of the VAIC commands different values compared to the aggregate measure, which implies that investors place different value on the three VAIC components. The results also indicate that physical capital efficiency is the most significant variable related to profitability while human capital efficiency is of great importance in enhancing the productivity of the company. This study concludes that VAIC can explain profitability and productivity but fails to explain market valuation.